Tectonothermal events in the Olympic IOCG Province constrained by apatite and REE-phosphate geochronology. Issue 5 (4th July 2018) - Cherry, A. R.; Kamenetsky, V. S.; McPhie, J.; Thompson, J. M.; Ehrig, K.; Meffre, S.; Kamenetsky, M. B.; Krneta, S.
ABSTRACT: The Olympic iron oxide–copper–gold province in South Australia contains numerous deposits and prospects, including the Olympic Dam Cu–U–Au–Ag deposit and the Acropolis prospect. The Acropolis prospect comprises massive, coarse-grained magnetite–apatite veins partly replaced by a hematite-stable assemblage. The apatite grains in the veins contain zones with abundant inclusions of other minerals (including monazite and xenotime) and low trace-element concentrations relative to the inclusion-free zones. The inclusion-rich apatite zones are interpreted to be formed from the recrystallisation of the inclusion-free apatite and remobilisation of U, Th and rare earth element (REE) from apatite into monazite and xenotime. Apatite, monazite and xenotime are all established U–Th–Pb geochronometers and offer the potential to constrain the alteration history of the Acropolis prospect. The LA-ICPMS U–Pb age of inclusion-free apatite is within error of the age of the host volcanic units ( ca 1.59 Ga). Inclusion-rich apatite yields both near-concordant analyses that are within error of the inclusion-free apatite as well as highly disturbed (discordant) analyses. The most concordant analyses of monazite (Th–Pb) inclusions and xenotime (U–Pb) inclusions and rim grains indicate an alteration event occurred at ca 1.37 Ga and possibly also at ca 500 Ma. The disparity in age of the inclusion-rich apatite and the REE-phosphate inclusions (and rim grains) is suggested to be owing to the apatite being initially recrystallised at ca 1.59 Ga and modified again by a later event that also formed (or coarsened) most of the inclusions. Partial resetting of the majority of the monazite inclusions as well as the presence of significant amounts of common Pb has complicated the interpretation of the monazite results. In contrast, xenotime is a more robust geochronometer in this setting. The ages of the two post-1.59 Ga events that appear to have affected the Acropolis prospect do not correspond to any events known to have occurred in the Gawler Craton. The earlier ( ca 1.37 Ga) age instead corresponds best with metamorphic–magmatic–hydrothermal activity in Laurentia, consistent with the proximity of Laurentia and the Gawler Craton inferred from palaeogeographic reconstructions. The later ( ca 500 Ma) event corresponds to the Delamerian Orogeny and has been shown by prior studies to have also affected the Olympic Dam deposit.